2017
DOI: 10.1038/s41467-017-00672-8
|View full text |Cite
|
Sign up to set email alerts
|

Rational development of catalytic Au(I)/Au(III) arylation involving mild oxidative addition of aryl halides

Abstract: The reluctance of gold to achieve oxidative addition reaction is considered as an intrinsic limitation for the development of gold-catalyzed cross-coupling reactions with simple and ubiquitous aryl halide electrophiles. Here, we report the rational construction of a Au(I)/Au(III) catalytic cycle involving a sequence of Csp2–X oxidative addition, Csp2–H auration and reductive elimination, allowing a gold-catalyzed direct arylation of arenes with aryl halides. Key to this discovery is the use of Me-Dalphos, a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
247
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(257 citation statements)
references
References 61 publications
10
247
0
Order By: Relevance
“…Alternatively,afew investigations have indicated that even in the absence of activation by light and external oxidants, aryl diazonium salts can be used as the coupling partners to perform certain CÀCc ross-coupling reactions. [233] Chem.E ur.J.2020, 26,1442 -1487 www.chemeurj.org Extending the scope of Au redox catalysis with aryl diazonium salts, Shi'sg roup have developed Sandmeyer-type reactions for the generationo fC ÀY( Y = Br,S ,a nd P) bonds (Scheme 40). [237] Pivotal to the successo ft he reactions was the use of 2,2'-bipyridine (bpy) ligand and the base Na 2 CO 3 .T he mechanistic studies revealed that Na 2 CO 3 assists the formation of an initial alkynyl or arylgold complex.T his Au complex bonds to the aryl-diazonium salts to produce an Au III intermediate.…”
Section: Oxidant-free Oxidative Addition Of C-heteroatom Bonds To Au mentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively,afew investigations have indicated that even in the absence of activation by light and external oxidants, aryl diazonium salts can be used as the coupling partners to perform certain CÀCc ross-coupling reactions. [233] Chem.E ur.J.2020, 26,1442 -1487 www.chemeurj.org Extending the scope of Au redox catalysis with aryl diazonium salts, Shi'sg roup have developed Sandmeyer-type reactions for the generationo fC ÀY( Y = Br,S ,a nd P) bonds (Scheme 40). [237] Pivotal to the successo ft he reactions was the use of 2,2'-bipyridine (bpy) ligand and the base Na 2 CO 3 .T he mechanistic studies revealed that Na 2 CO 3 assists the formation of an initial alkynyl or arylgold complex.T his Au complex bonds to the aryl-diazonium salts to produce an Au III intermediate.…”
Section: Oxidant-free Oxidative Addition Of C-heteroatom Bonds To Au mentioning
confidence: 99%
“…[233] They used Me-Dalphos ligands containing Pa nd Ng roups, which can assist the oxidative addition process, as hasb een revealed from DFT studies (Scheme 38). [233] They used Me-Dalphos ligands containing Pa nd Ng roups, which can assist the oxidative addition process, as hasb een revealed from DFT studies (Scheme 38).…”
Section: Oxidant-free Oxidative Addition Of C-heteroatom Bonds To Au mentioning
confidence: 99%
See 1 more Smart Citation
“…[33] Gold(III) intermediates generated after oxidative addition of arylÀXt oA u I /phosphine compounds are also widely used for aryl transfer and C À Cc oupling, [34] while gold(I)-catalyzed oxidative allene-thiol coupling leads to the formation of vinyl sulfide alcohols. [33] Gold(III) intermediates generated after oxidative addition of arylÀXt oA u I /phosphine compounds are also widely used for aryl transfer and C À Cc oupling, [34] while gold(I)-catalyzed oxidative allene-thiol coupling leads to the formation of vinyl sulfide alcohols.…”
mentioning
confidence: 72%
“…Second, in 2013, Glorious and co‐workers reported the Au I oxidation with aryldiazonium salts combined with a Ru photoredox catalyst, leading to the development of new methodologies for gold‐catalyzed arylation (Scheme b) . Third, in 2017, in Bourissou's group, aryl halides were used in the gold‐catalyzed arylation of electron‐rich arenes by hemilabile P,N ligand‐promoted oxidative addition of gold(I) (Scheme c) . However, these strategies suffered from some drawbacks, for example the steps for the synthesis of the hypervalent iodine reagents, the low atom efficiency (only a small part of the reagent is transferred or more than one equivalent of silver is required) and the need of complicated bidentate ligands.…”
Section: Methodsmentioning
confidence: 99%